Biomarkers Are Associated With Clinical and Endoscopic Outcomes With Vedolizumab Treatment in Ulcerative Colitis. Issue 2 (5th October 2018) - Battat, Robert; Dulai, Parambir S; Vande Casteele, Niels; Evans, Elisabeth; Hester, Kelly D; Webster, Edvelyn; Jain, Anjali; Proudfoot, James A; Mairalles, Ara; Neill, Jennifer; Singh, Siddharth; Chang, John T; et al.
Abstract: Background: Vedolizumab inhibits α4β7-mediated lymphocyte trafficking and is effective in ulcerative colitis (UC). This study evaluated drug and biomarker concentrations and patient outcomes during vedolizumab treatment in UC. Methods: Prospectively scored maintenance clinical (26.5 weeks; interquartile range [IQR], 16.3–37.0 weeks) and endoscopic (23.5 weeks; IQR, 16.8–35.6 weeks) outcomes were compared with serum vedolizumab concentrations, antivedolizumab antibodies, and serum biomarkers at baseline and weeks 2, 6, 14, and 26. A linear mixed-effects model compared biomarker trajectories over time between clinical and endoscopic remitters and nonremitters. Results: Thirty-two patients were included. Soluble (s)–tumor necrosis factor (TNF)–α, s-α4β7, s-mucosal addressin cell adhesion molecule (s-MAdCAM-1), and s-amyloid A (s-AA) significantly changed with treatment. A linear mixed-effects model demonstrated that s-α4β7 ( P = 0.044) increased and s-MAdCAM-1 ( P = 0.006) and s-vascular cell adhesion molecule-1 (s-VCAM-1, P = 0.001) decreased more rapidly in patients achieving clinical remission in maintenance. S-MAdCAM-1 ( P = 0.005), s-intracellular adhesion molecule-1 (ICAM-1; P = 0.014), s-VCAM-1 ( P < 0.001), and s-TNF ( P = 0.052) decreased more rapidly in endoscopic remitters. In clinical remitters, higher week 14 (20.3 ng/mL vs 6.0 ng/mL; P = 0.013) and week 26 (14.1 ng/mL vs 8.6 ng/mL; P = 0.05) s-α4β7 were observed. In endoscopic remitters, week 2 (6.7 pg/mL vs 17.8 pg/mL; P = 0.038) and week 6 (3.9 pg/mL vs 15.6 pg/mL; P = 0.005) s-TNF and week 14 s-VCAM (589.1 ng/mL vs 746.0 ng/mL; P = 0.05) were lower. Conclusion: Serum biomarkers were associated with outcomes in vedolizumab-treated UC patients. s-α4β7 increased, whereas s-MAdCAM-1, s-VCAM-1, s-ICAM-1, and s-TNF decreased more rapidly in remitters. At individual time points, induction s-TNF and maintenance s-VCAM-1 concentrations were lower, whereas maintenance s-α4β7 concentrations were higher in remitters.